Nephropathy in a child suffering from tetralogy of Fallot - Naik, Vrushank Santosh; Phadke, Varsha Dilip; Kanhere, Sujata Vishnu (Indian Journal of Case Reports, 2020)
Cyanotic nephropathy is a type of renal impairment, occurring due to chronic exposure to hypoxia, seen in unoperated cases of cyanotic congenital heart diseases (CCHDs). Due to a paucity of the literature and lack of general awareness of this condition, many times, the occurrence of this nephropathy is left untreated, leading to chronic kidney disease (CKD). The mortality rate is 51% in children who suffer from CCHD with CKD. Here, we report a case of an 11-year-old male child with tetralogy of Fallot (unoperated), requiring repeated admissions for breathlessness. An incidental finding of proteinuria on multiple admission was further investigated. The patient had hemoconcentration with deranged renal function tests, [hypoalbuminemia (2.2 gm/dl), serum creatinine 3.4 mg/dl, eGfR 16.28, and urine protein:creatinine ratio 3.95]. USG KUB done reported a bilateral medicorenal disease with a complete loss of corticomedullary differentiation. The patient already had Stage IV CKD at the time of presentation and expired 8 months after diagnosis.